Development of an aggregated social inclusion indicator. Disparities in the European Union on inclusion/exclusion social determined with social inclusion index - Paraschiv, Dorel-Mihai; Manea, Daniela-Ioana; Țițan, Emilia; Mihai, Mihaela (Technological and Economic Development of Economy, 2021)
When we mention social inclusion, most of us think of political participation, social rights, civil liberties, equal access to race, ethnicity and gender, access to social services and the labour market, basically to a broader concept than social development. Social inclusion is a concept that can actually be defined, which means it can probably be measured. On this basis, a continuous effort is being made to measure the social inclusion elements, so the results can be used to build new indicators that help measure the multiple dimensions of social inclusion: The Social Inclusion Index, the Human Opportunity Index. This paper presents the development, based on multivariate data analysis techniques and methods, of an aggregated indicator of social inclusion for the member countries of the European Union which, besides the traditional variables (GDP), also measures the factors related to civil and political rights, women’s rights or perception of the LGBT community. First published online 06 October 2021